2018
DOI: 10.7151/dmgt.2049
|View full text |Cite
|
Sign up to set email alerts
|

Equitable coloring and equitable choosability of graphs with small maximum average degree

Abstract: A graph is said to be equitably k-colorable if the vertex set V (G) can be partitioned into k independent subsets V 1 , V 2 ,. .. , V k such that ||V i | − |V j || ≤ 1 (1 ≤ i, j ≤ k). A graph G is equitably k-choosable if, for any given k-uniform list assignment L, G is L-colorable and each color appears on at most |V (G)| k vertices. In this paper, we prove that if G is a graph such that mad(G) < 3, then G is equitably k-colorable and equitably kchoosable where k ≥ max{∆(G), 4}. Moreover, if G is a graph such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In [12] it is shown that Conjectures 3 and 4 hold for forests, complete bipartite graphs, connected interval graphs, and 2-degenerate graphs with maximum degree at least 5. Conjectures 3 and 4 have also been verified for outerplanar graphs [24], series-parallel graphs [22], graphs with small maximum average degree [3], powers of cycles [9], and certain planar graphs (see [2], [13], [23], and [25]). In 2013, Kierstead and Kostochka made substantial progress on Conjecture 3, and proved it for all graphs of maximum degree at most 7 (see [11]).…”
Section: Conjecture 3 ([12]) Every Graph G Is Equitablymentioning
confidence: 80%
See 1 more Smart Citation
“…In [12] it is shown that Conjectures 3 and 4 hold for forests, complete bipartite graphs, connected interval graphs, and 2-degenerate graphs with maximum degree at least 5. Conjectures 3 and 4 have also been verified for outerplanar graphs [24], series-parallel graphs [22], graphs with small maximum average degree [3], powers of cycles [9], and certain planar graphs (see [2], [13], [23], and [25]). In 2013, Kierstead and Kostochka made substantial progress on Conjecture 3, and proved it for all graphs of maximum degree at most 7 (see [11]).…”
Section: Conjecture 3 ([12]) Every Graph G Is Equitablymentioning
confidence: 80%
“…Conjecture 2 has been proven true for interval graphs, bipartite graphs, outerplanar graphs, subcubic graphs, certain planar graphs, and several other classes of graphs (see [1], [2], [3], [14], [15] and [21]).…”
Section: Theorem 1 ([6]mentioning
confidence: 99%
“…In [13] it is shown that Conjectures 3 and 4 hold for forests, complete bipartite graphs, connected interval graphs, and 2-degenerate graphs with maximum degree at least 5. Conjectures 3 and 4 have also been verified for outerplanar graphs [25], series-parallel graphs [23], graphs with small maximum average degree [3], certain graphs related to grids [4], powers of cycles [10], and certain planar graphs (see [2,14,24] and [26]). In 2013, Kierstead and Kostochka made substantial progress on Conjecture 3, and proved it for all graphs of maximum degree at most 7 (see [12]).…”
Section: Equitable Choosabilitymentioning
confidence: 90%
“…Conjecture 2 has been proven true for interval graphs, bipartite graphs, outerplanar graphs, subcubic graphs, certain planar graphs, and several other classes of graphs (see [1,2,3,15,16] and [22]).…”
Section: Conjecture 2 ([1] ∆-Ecc)mentioning
confidence: 99%
“…Their conjecture is still open and is known as the ∆-Equitable Coloring Conjecture (∆-ECC for short). It has received considerable attention in the literature (see e.g., [5,8,9,17,18,27]).…”
Section: Equitable Coloring and Equitable Choosabilitymentioning
confidence: 99%